2017
DOI: 10.3389/fpsyg.2017.01343
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 8- and 4-Session Mindfulness-Based Interventions in a Non-clinical Population: A Controlled Study

Abstract: Background: Many attempts have been made to abbreviate mindfulness programmes in order to make them more accessible for general and clinical populations while maintaining their therapeutic components and efficacy. The aim of this study was to assess the efficacy of an 8-week mindfulness-based intervention (MBI) programme and a 4-week abbreviated version for the improvement of well-being in a non-clinical population.Method: A quasi-experimental, controlled, pilot study was conducted with pre-post and 6-month fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 62 publications
1
66
0
16
Order By: Relevance
“…Participants randomised to the intervention attended a median of seven sessions (inter-quartile range 2-7) including one person who attended no sessions at all, and six students who attended all the sessions. Eighteen participants (67% of those randomised to the intervention) attended at least half of the mindfulness course sessions, our pre-specified "minimum dose" 42 also used in previous studies 43 , and shown to produce meaningful change 44 . Three participants provided reasons for abandoning their mindfulness course; these were schedule conflicts or being too busy.…”
mentioning
confidence: 99%
“…Participants randomised to the intervention attended a median of seven sessions (inter-quartile range 2-7) including one person who attended no sessions at all, and six students who attended all the sessions. Eighteen participants (67% of those randomised to the intervention) attended at least half of the mindfulness course sessions, our pre-specified "minimum dose" 42 also used in previous studies 43 , and shown to produce meaningful change 44 . Three participants provided reasons for abandoning their mindfulness course; these were schedule conflicts or being too busy.…”
mentioning
confidence: 99%
“…Such reduction to four sessions has also been conducted in some studies that have suggested using mindfulness for preventive purposes (Manotas, Segura, Eraso, Oggins, & McGovern, ; Nitzan‐Assayag et al, ; Pigeon, Allen, Possemato, Bergen‐Cico, & Treatman, ; Possemato et al, ). In this sense, Demarzo et al () did not find significant differences between a standard program of intervention in mindfulness of 8 weeks versus a shortened protocol of 4 weeks, reporting a similar efficacy in its positive effects. Based on these resources, a brief program of basic skills training in mindfulness was designed.…”
Section: Methodsmentioning
confidence: 96%
“…However, similar results were found using objective electronic measurement in a sixweek MBCT-based program that showed that adherence to practice (length, frequency, and type of meditation chosen) did not relate to outcomes 73 . Recently, a first study to directly compare an 8-week with a 4-week MBI showed improvements compared to controls in mindfulness and positive affect, but not between the 4-week and 8-week MBI 74 . Thus, abbreviated MBI might be similar to a standard MBI.…”
Section: Future Directions and Considerationsmentioning
confidence: 99%